Optimasi Dana Wakaf Produktif dengan MATLAB: Studi pada Badan Wakaf UII Yogyakarta - Rismawati Rismawati; Rahman Mutamam; Triana Apriani (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This study discusses the optimization of the allocation of productive waqf funds using MATLAB through a case study on the Waqf Board of the Islamic University of Indonesia (UII) Yogyakarta. Productive waqf has an important role in supporting socio-economic empowerment, but its management often faces challenges in determining the efficient distribution of funds. The purpose of this research is to develop a mathematical model to optimize the allocation of waqf funds in various sectors such as education, health, micro enterprises, and social programs. The research method uses a quantitative approach with optimization techniques implemented in MATLAB to simulate various fund distribution scenarios. The results of the study show that the optimization model is able to provide a more effective distribution of waqf funds compared to the actual allocation pattern, thereby increasing efficiency and impact on community welfare. Thus, the use of MATLAB has been proven to help waqf institutions in formulating accurate data-based decisions and mathematical models. In addition, this study emphasizes that the application of modern computing technology can strengthen the role of waqf as an instrument of sustainable social development. The implications of this study show that the integration of mathematical modeling with modern computing tools can be an important strategy for Islamic philanthropic institutions in maximizing the potential of productive waqf, especially in Yogyakarta. This research also contributes to the development of Islamic economic literature, offers practical recommendations for waqf managers, and shows the application of MATLAB as a tool in economic decision-making. With this approach, productive waqf is expected to provide wider and sustainable benefits for the community, as well as be an inspiration for other waqf institutions in Indonesia to adopt a similar strategy.